Case report: Clinical characteristics and genetic analysis of a familial platelet disorder associated with RUNX1 gene mutation - Zhou, Hua; Zhao, Jing; Gu, Xiaoyan (Frontiers in Hematology, 2025)
ObjectiveTo explore the clinical and genetic mutation characteristics of familial platelet disorder with acute myeloid leukemia tendency (FPD/AML) caused by RUNX1 germline mutations.MethodsThe clinical data and gene mutation results of a child with FPD/AML and family members admitted to Changzhou Children’s Hospital on 8 September 2022 were analyzed.ResultsA 1-year and 11-month-old male patient had recurrent thrombocytopenia for 1 year, with scattered bleeding points throughout the body. Blood routine tests showed thrombocytopenia, and peripheral blood smears and bone marrow cytology tests showed no significant abnormalities. The gene sequencing results showed that the patient carried a frameshift mutation in RUNX1: c.494delG (p.G165Vf*11). Sanger sequencing, which was used for family verification analysis, revealed that the mutation in the patient was inherited from his mother, and his grandmother had similar clinical symptoms.ConclusionsThese findings expand the spectrum of RUNX1 variants linked to familial platelet disorders. The familial platelet disorder (FPD) associated with this gene is clinically rare and has the potential to undergo malignant transformation. Continuous monitoring of biological evolution is essential, and early intervention and treatment may be warranted.